Journey to St Patrick's Purgatory - Boyd, Stephen (Textos B Ser., 2022)
In autumn 1397, Viscount Ramon de Perellós, a Catalan nobleman, soldier and diplomat, left the papal palace in Avignon to travel to St Patrick's Purgatory, famous throughout Europe as a gateway to the next world. There, he spent twenty-four hours in an underground cavern, where he claimed to have travelled through the nine fields of Purgatory, accompanied by demons, before entering the Earthly Paradise and catching a glimpse of Heaven.